Medicalização do parto: a apropriação dos processos reprodutivos femininos como causa da violência obstétrica - Kenia Martins Pimenta Fernandes; Carlos Mendes Rosa (Ciências Sociais Unisinos)
The discussion proposed in this article is the result of a qualitative research based on a bibliographic review, with the objective of uncovering the historical outline of the process of medicalization of childbirth, verifying its influence in the appropriation of female reproductive systems and the consequent reduction of women’s autonomy over their own bodies, and of pointing out women’s humans rights violations that have occurred since then that must be recognized as obstetric violence. Childbirth, conducted in western societies exclusively by midwives until mid-16th century, became medicalized and institutionalized in the second half of the 20th century. The medicalization of childbirth, as a result of social medicalization that attributes medical and pathological characteristics to natural aspects of life, was marked by the removal of midwives from the management of labor, which then became a predominantly male knowledge, given the prohibition of formal education for women. Misoginy and the determinant moral and religious aspects in society led to the objectification of the female body as an artifice of medical learning and a means of practicing population control. The medicalization process gave rise to a form of violence resulting from the appropriation of female reproductive processes by health teams called obstetric violence, characterized by the use of harmful obstetric practices that lack scientific evidence of its effectiveness, which are permeated gender and social class prejudices and institutional racism. These aspects are among the main obstacles to dealing with obstetric violence, which needs to be looked at in an intersectional manner, with a focus on women’s autonomy regarding their bodies, taking into account the different forms of oppression to which they are subjected.